High-isolation microstrip two-port diplexer and full-duplex antenna with metamaterial-based filters - Al Gburi, Ahmed Jamal Abdullah; Elabd, Rania Hamdy; Amr Hussein, Hussein Abdullah (Springer Nature, 2025)
This article presents an efficient and novel design of a microstrip three-terminal diplexer and a two-port full-duplex antenna system incorporating metamaterial-based filtering techniques to achieve high isolation and low insertion loss. Conventional diplexers and full-duplex antennas often suffer from excessive insertion loss, strong mutual coupling, and insufficient isolation, which limit their performance in modern wireless communication systems. To address these challenges, a compact 100×25.5 mm² diplexer is designed using a T-junction combiner to integrate two square open-loop resonator (SOLR)-based band-pass filters (BPFs) tuned to distinct frequencies. To enhance isolation and minimize undesired substrate coupling, metamaterial-inspired structures—specifically, four defected ground structure (DGS) cells and complementary square ring resonator (CSRR) BPFs—are incorporated. These engineered components effectively suppress surface wave propagation, enhance selectivity, and mitigate unwanted interference, resulting in superior isolation performance. Consequently, the diplexer achieves exceptional port isolation levels of −65 dB and −90 dB, with identical fractional bandwidths of 2.5%, and low insertion losses of −1.09 dB and −1.13 dB at the transmission (2.51 GHz) and reception (2.81 GHz) frequencies, respectively. To further enhance system functionality, the diplexer is integrated with a wideband Mickey-shaped patch antenna featuring a partial ground plane, ensuring bidirectional radiation, stable gain, and efficient impedance matching. The performance of the proposed system is validated through full-wave simulations and experimental measurements, showing strong agreement between theoretical and measured results.